2023
DOI: 10.1128/spectrum.03961-22
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Drug Addiction and Detoxification on the Human Oral Microbiota

Abstract: Drug addiction has serious negative consequences for human health and public security. The evidence indicates that drug abuse can cause poor oral health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…The oral cavity provides a highly heterogeneous ecological niche for microorganisms, and the damage to the oral microbial community caused by drug addiction is generally not permanent [9]. In our study, as one of the dominant phyla of oral microbiota observed in METH addicts, Firmicutes were revealed with signi cant changes of reduced alpha diversity, microbial community shifts, and alterations in the abundance of individual taxa.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The oral cavity provides a highly heterogeneous ecological niche for microorganisms, and the damage to the oral microbial community caused by drug addiction is generally not permanent [9]. In our study, as one of the dominant phyla of oral microbiota observed in METH addicts, Firmicutes were revealed with signi cant changes of reduced alpha diversity, microbial community shifts, and alterations in the abundance of individual taxa.…”
Section: Discussionmentioning
confidence: 53%
“…Recently, Zhang et al found that METH addiction caused a decrease in alpha diversity of the oral microbiota and an increase in alpha diversity during detoxi cation with Bacteroidetes identi ed as the dominant phylum and a group of ve key microorganisms (i.e., Neisseria sub ava, Haemophilus parain uenzae, Fusobacterium periodonticum, Prevotella melaninogenica, and Veillonella dispar) involved in in uencing the mechanisms regulating the METH addiction, providing high predictive accuracy for differentiating METH addicts based on a random forest classi er [9]. However, our study revealed different variations in oral microbiota, probably due to (1) the varied geographical sources of the samples, and (2) the length of detoxi cation, the smoking status, and the oral health of the participants, which could affect the compositions of the oral microbiota [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the toxicity damage caused by METH is closely related to the gut microbiome, and could be treated in mouse models by regulating the metabolites derived from the gut microbiome ( 8 ). Studies have also found that addiction to METH smoking can disrupt the balance of the human oral microbiome, characterized by decreased microbial diversity, while the oral microbiome is improved during the detoxification process ( 9 ). Furthermore, the oral microbiomes are also closely related to systemic diseases such as gastrointestinal and cardiovascular disorders ( 10 ).…”
Section: Introductionmentioning
confidence: 99%